Private registry's: New opportunities for sport organizations - Sobreiro, P. (International Journal of Computer Science in Sport, 2002)
The development of Internet helped various organizations putting their presence online. With the increase of sport organizations on Internet, new problems emerged and new methods are needed to solve the heterogeneity of the existing systems.